Relationship between Pre-Eclampsia, Renal Impairment and Hepatic Insufficiency among Pregnant Women in Al-Jouf Area - Omnia Magdy Hendawy; Shaimaa Hussein; Eman A. Harahsheh (Journal of Pharmacy and Nutrition Sciences, 2020)
Background: Pre-eclampsia is a pregnancy-specific syndrome. It affects 3-5% of pregnant women and is characterized by oedema, high blood pressure, and proteinuria. Moreover, in women with pre-eclampsia dysfunction of many organs, such as kidney and liver, is diagnosed, while in the case of foetus growth restriction is observed. Pre-eclampsia, when left untreated, can lead to a high mortality rate. In low-income countries, this disorder is one of the main causes of maternal and child mortality. Pre-eclampsia predisposes women in later life to cardiovascular diseases. So far, in acute cases of pre-eclampsia stabilization of the mother and fotus, and finally, termination of pregnancy at a time optimal for both sides can only be considered. Methods: The present work is designed to investigate the relationship between pre-eclampsia, renal and hepatic insufficiency in the Al-Jouf area through collecting information from the electronic database of maternity hospital for 100 pregnant women who suffered from pre-eclampsia compared with normal pregnancies. Results: The prevalence of pre-eclampsia is more prone in eldest women (older than 35 years old) almost 45% than younger women (20-25 years old), PC to MPV ratio value showed a significant suppression in pre-eclamptic pregnancies in comparison with normal pregnant women while HbA1c % value indicated a significant increase in the pre-eclamptic cases than the healthy pregnant women. Renal indices, serum creatinine, urea, and albumin were significantly higher in the pre-eclamptic women than in women with normal pregnancies. Conclusion: There is a tight relationship between hypertensive disorders during pregnancies, chronic renal disorders and hepatic insufficiency.